2014
DOI: 10.1017/jmo.2014.50
|View full text |Cite
|
Sign up to set email alerts
|

The influence of HR practices and job satisfaction on interpersonal deviance in the workplace

Abstract: We examined the influence of human resource practices on interpersonal deviance at work through job satisfaction. A survey was carried out among 372 manufacturing employees of various occupational levels in manufacturing companies in the northern region of Malaysia. We collected data by distributing questionnaires to participants, with the assistance of human resource department. We asked them to indicate how often they know whether any of their workmates engaged in different types of interpersonal deviance. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…That is, a negative behavioural response to a lack of happiness feels warranted and limits further resource losses, by making employees feel less bad about their career (Hobfoll and Shirom, 2000). Similarly, employees who find little enjoyment in the execution of their job tasks may attribute these negative feelings to a lack of organizational support for their personal well-being (Bowling, 2010; Shamsudin et al, 2014). In turn, they can avoid additional resource losses by releasing the negative energy that comes with this attribution, through dysfunctional work activities that threaten the well-being of their organization or its members (Fox and Spector, 2006; Taylor et al, 2017).…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, a negative behavioural response to a lack of happiness feels warranted and limits further resource losses, by making employees feel less bad about their career (Hobfoll and Shirom, 2000). Similarly, employees who find little enjoyment in the execution of their job tasks may attribute these negative feelings to a lack of organizational support for their personal well-being (Bowling, 2010; Shamsudin et al, 2014). In turn, they can avoid additional resource losses by releasing the negative energy that comes with this attribution, through dysfunctional work activities that threaten the well-being of their organization or its members (Fox and Spector, 2006; Taylor et al, 2017).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…With its empirical focus on the country of Pakistan, this study also addresses the need for research into the harmful behavioural outcomes of negative job situations in understudied, non-Western settings (Alias et al, 2013; Biswas, 2016; Liu et al, 2010; Shamsudin et al, 2014). Pakistani culture is marked by high levels of uncertainty avoidance (Hofstede et al, 2010), so uncertainty-invoking job dissatisfaction might have a particularly strong effect on Pakistani employees’ desire to vent their negative job energy through deviant behaviours (Bowling, 2010; Judge et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While a survey done by Ramayah (2010) in one of the companies in Malaysia showed the employees in average spent 25% of the daily work time to access Internet materials for personal use. Studies also showed that cyberloafing could lower performance and productivity of a company (Al-shuaibi et al, 2014); and some employees cannot complete their task due to over cyberloafing and it decreases their work productivity (Lim & Chen, 2012); and lastly it is against work ethnics and harmful to organization (Al-shuaibi et al, 2014;Banerjee & Singh, 2015). Thus, some organization took action to ban the usage of cell phones in office during working hours due to its high potential effects on customers service (Kidwell, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…There are a few terms which are being used under the same definition of cyberloafing by different researchers across this field, such as "cyberslacking" (O'Neill, Hambley, & Chatellier, 2014), "cyberdeviance" (Al-shuaibi, Subramaniam, & Mohd Shamsudin, 2014;Blanchard & Henle, 2008), personal web usage "PWU" (Mahatanankoon, Anandarajan, & Igbaria, 2004). Sometimes, the employees do not use Internet to do their job during working hours, but use it for personal matter.…”
Section: Negative Impact Of Internet ~ Cyberloafing?mentioning
confidence: 99%
“…Previous research confirms this conviction. It has been demonstrated that personnel activities limit deviance (Woodrow and Guest, 2014; Shamsudin et al , 2014).…”
Section: Conceptual Framework and Related Literaturementioning
confidence: 99%